1992
DOI: 10.1017/s0022215100119498
|View full text |Cite
|
Sign up to set email alerts
|

Simple method of insertion of Xomed one piece septal button

Abstract: Silicone septal buttons have been available to obturate septal perforations since the 1970s. Various methods of insertion have been suggested but the procedure is not always easy. We have devised an alternative method which has proved quick and simple to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Septal button insertion for NSP has been well‐described in the literature using various techniques and materials . For example, there have been reports describing cutting a large, straight slit in a single flange . Another method modifies this slit technique by suggesting a small radial cut across the flange and using two forceps for insertion .…”
Section: Discussionmentioning
confidence: 99%
“…Septal button insertion for NSP has been well‐described in the literature using various techniques and materials . For example, there have been reports describing cutting a large, straight slit in a single flange . Another method modifies this slit technique by suggesting a small radial cut across the flange and using two forceps for insertion .…”
Section: Discussionmentioning
confidence: 99%
“…Kelly et al suggested sewing the flange in a purse string fashion, and then applying traction so that the disc assumes a concertina shape, thus making it small enough to pass through the perforation 5. Al‐Khabori suggested trimming the edges and making a radial slit in one of the flanges to facilitate insertion of the septal button 2. However, with the radial cut we found it difficult to deliver the flange across the perforation.…”
Section: Discussionmentioning
confidence: 99%
“…The main problem with the silicone button is the insertion of flange through the septal perforation, especially when the perforation size is relatively small. Some authors recommend trimming the edges of the silicone button, but that may result in traumatizing the perforation edge 2. Kelly et al suggested sewing the flange in a purse string fashion, and then applying traction so that the disc assumes a concertina shape, thus making it small enough to pass through the perforation 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One technique suggested making a radial cut to allow the disk to be rotated into position. 2 This still required a degree of intranasal manipulation. Other techniques use customized designs 3 that may not be readily available in all departments or that require special prosthetic techniques.…”
Section: Discussionmentioning
confidence: 99%